Management effectiveness in national parks from Peru - Toro, Arlan Jack Coronel (2021)
The unsustainable exploitation of natural resources in protected areas has increased globally and at an accelerated rate in the 21st century, mainly in tropical regions such as South America. This scenario has worried the scientific community, due to the risks of loss of biodiversity and ecosystem functions, while at the same time there is a growing urgency for the inspection and maintenance of these areas. In this context, the central objective of this work was to evaluate the management effectiveness of national parks in Peru. For this, the scenario matrix was used, which is based on the application of a questionnaire to park managers. The methodology establishes possible scenarios based on a set of indicators, thus generating the result of park management effectiveness (unsatisfactory to satisfactory). Most parks (6 or 55%) showed medium management effectiveness and 45% (5 parks) of the parks showed satisfactory management effectiveness. The effectiveness found is explained by the positive performance of the indicators expropriation, relationship with the surroundings, protection and inspection programs, and management plan. Also, there is no significant difference in the importance of the indicators for the final answers on the effectiveness of park management. Our results indicate that Peru's national parks are currently well managed. However, some indicators need to be improved, especially for parks that showed medium management effectiveness. Furthermore, this study can help managers to maintain and allocate financial resources in protected areas with greater precision, since the scenario matrix methodology allows the identification of low performance indicators. Keywords: Protected natural areas. Scenario matrix. Performance indicators.